â€FAKTOR-FAKTOR YANG MENYEBABKAN TENAGA KERJA INDONESIA YANG BEKERJA DI MALAYSIA DAN DIPULANGKAN KE DAERAH ASALâ€ - B21107029, SAMSUL HADI (Jurnal Pembangunan dan Pemerataan, 2014)
The placement of Indonesian workers abroad by the decree of Ministry of Manpower and Transmigration of the Republic of Indonesia number KEP-104A/MEN/2002 is a national program as an effort to improve the welfare of workers and their families as well as the development of human resources. The problem in this study is what factors that cause migrants being deported from Malaysia. Of these problems researchers interested in studying more about Factor-Factor OF INDONESIA LABORSWHO WERE DEPORTED FROM MALAYSIA. The purpose of this study is exploratory studies that focus on to determine the factors that cause Indonesian migrants workers being deported from Malaysia. The result of this study is characteristic of Indonesian Workers that works in Malaysia which is dominated by men (67%,) while the majority of respondents aged 21-30 years old, 47% high school educated migrant workers, the average monthly income of Rp.1.600. 000, - Rp.2.000.000, - while the income / wage workers in Malaysia by Rp.2.400.000, - Rp.3.000.000, -. The factors that cause migrants being deported from Malaysia are completeness of document (54%), jobless (34%), completeness of manpower documents (54%), wage reduced (52%), workers only received 68% of total wages for work in Malaysia), improperly treatment with either by employers (52%), escape (48%), having violence experience while working in Malaysia (69%) and 79% workers were recommended by a person to work as migrant workers. The government and Indonesian private company of employment were expected to continue in maintaining and implementing serious training information for prospective workers (domestic workers) who are sent abroad. As for formal workers do training through Training Center owned by the government. Government asked to be firm in dealing with violence against Indonesian worker. The government, which is Â represented by the Ministry of Foreign Affairs should provide protection for citizens who were deported, especially since they are abroad in order to avoid massive deportations that eventually give rise to new problems for the receiving area.